How history and ideology affect political preferences in Russia - Onay, Yaşar (Kastamonu Üniversitesi, 2026)
This article looks at how political preferences in Russia are shaped not only by short-term propaganda, but mainly by long historical experiences and powerful stories about sovereignty, security, and the role of the state. The argument is that Russian society, after centuries of imperial rule, decades of Soviet mobilization, and the chaotic 1990s, has learned to expect strong centralized authority as the main guarantee of order and stability. This is less about people being misled and more about a cultural habit formed over generations. The study uses academic literature, surveys from the Levada Center, and an analysis of official narratives. It shows that collective memory—of the October Revolution, the victory in World War II, and the collapse of the Soviet Union—shapes how Russians think about politics today. These memories make strong leadership appear normal and even necessary. In other words, history is not just in the background; it actively shapes how people see the present. The article also finds clear differences between generations and regions. Older people and those living outside major cities usually value stability, predictability, and state protection. Younger, urban Russians are exposed to different media and global ideas, and they sometimes hold more liberal views. Yet they often feel cynical, distrust institutions, and stay away from active politics. As a result, elections in Russia often work less as a real competition and more as a ritual, a way of confirming the system. Leaders keep their legitimacy through what the article calls “narrative patriotism”: the use of external threats and ideas of national uniqueness to turn pride and past traumas into loyalty to authority. Looking ahead, the article sketches three possible futures for Russia after 2024: continued but suffocating stability, a carefully managed transition of power by elites, or a sudden crisis that breaks the system. Each path shows both the strengths and the fragility of the regime. In the end, the article argues that Russian political choices are rooted in memory and identity as much as in fear or material benefits. Support for strong leaders works as a cultural survival strategy, not just blind obedience. To understand Russia, we must see history as an active force in today’s politics.

Bu makale, Rusya‘da insanların siyasal tercihlerini yalnızca bugünün propagandasının değil, çok daha uzun bir tarihsel sürecin ve hafızada derin izler bırakan anlatıların şekillendirdiğini öne sürüyor. Rusya‘da siyaset, genellikle egemenlik, güvenlik ve devletin varlığı gibi duygusal konular etrafında algılanmaktadır. Halk, yüzyıllar boyunca yaşadığı deneyimler nedeniyle güçlü merkezi otoriteyi düzenin garantisi olarak görmeye alışmıştır. İmparatorluk döneminin otoriter mirası, Sovyet yıllarının topyekûn seferberliği ve 1990‘ların kaotik ortamı, bu beklentiyi daha da pekiştirmiştir. Bu nedenle güçlü devlet ve güçlü lider düşüncesi, yalnızca yöneticilerin dayattığı bir anlayış değil, halkın belleğinde kuşaktan kuşağa aktarılan bir refleks haline gelmiştir. Bu çalışmada, akademik kaynaklar, Levada Center‘ın anketleri ve resmi söylemlerin analizi bir araya getirilmiştir. Böylece Ekim Devrimi, Büyük Vatanseverlik Savaşı ve Sovyetler Birliği‘nin çöküşü gibi kritik olayların, günümüz Rus halkının zihninde nasıl şekillendiği ortaya çıkmaktadır. Bu kolektif hafıza, güçlü liderliği olağan ve gerekli bir şeymiş gibi sunmaktadır. Bulgular, toplum içinde kuşaklara ve bölgelere göre farklılıklar olduğunu da göstermektedir. Yaşlılar ve kırsalda yaşayanlar daha çok istikrar ve devletin korumasını önemserken, genç ve şehirli kesimler ise daha farklı bilgi kaynaklarına ve küresel değerlere ulaşabilmektedir. Buna rağmen bu gruplar arasında da siyasal hayal kırıklığı, kurumlara güvensizlik ve siyasetten uzak durma eğilimi öne çıkmaktadır. Seçimler de bu nedenle gerçek bir yarıştan çok, sistemi onaylayan birer tören gibi algılanmaktadır. Liderler ise dış tehdit söylemleri ve ―medeniyetimiz eşsizdir‖ vurgusu üzerinden meşruiyet kazanmakta, geçmişteki gurur ve travmalar bugünün iktidarına destek olarak geri dönmektedir. Bu çalışmada, 2024 sonrası için üç olası senaryo çizilmiştir. Boğucu bir istikrarın devamı, elitlerce yönetilen bir geçiş süreci ya da ani bir krizle sistemin sarsılması. Bu ihtimaller hem rejimin uyum yeteneğini hem de kırılganlığını gösteriyor. Sonuç olarak, Rusya‘da güçlü liderlere verilen destek, basit bir boyun eğme değil, tarihsel deneyimlerden doğan bir hayatta kalma stratejisidir. Tarih burada yalnızca geçmişin gölgesi değil, bugünü aktif olarak şekillendiren bir güç olarak karşımıza çıkmaktadır.
Rusya’daki politik tercihlere tarih ve ideolojinin etkisi
Keywords: Political culture; Historical memory; Authoritarianism; Russia; Putin era; Politik kültür; Tarihsel hafıza; Otoriterlik; Rusya; Putin dönemi